1997
DOI: 10.1016/s0092-8674(00)80424-9
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Chordin by Xolloid Metalloprotease Suggests a Role for Proteolytic Processing in the Regulation of Spemann Organizer Activity

Abstract: The Xolloid secreted metalloprotease, a tolloid-related protein, was found to cleave Chordin and Chordin/BMP-4 complexes at two specific sites in biochemical experiments Xolloid mRNA blocks secondary axes caused by chordin, but not by noggin, follistatin, or dominant-negative BMP receptor, mRNA injection. Xolloid-treated Chordin protein was unable to antagonize BMP activity. Furthermore, Xolloid digestion released biologically active BMPs from Chordin/BMP inactive complexes. Injection of dominant-negative Xoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
319
0
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(333 citation statements)
references
References 46 publications
9
319
0
5
Order By: Relevance
“…In the early X. laevis embryos, Tolloid/ BMP-1 is known to regulate the activity of BMP-4 by degrading Chordin (Piccolo et al, 1997;Wardle et al, 1999;Blitz et al, 2000;Balemans and Hul, 2002). In the remodeling X. laevis intestine, we have shown that the mRNA expression of both Tolloid/ BMP-1 and Chordin appears to be weaker but up-regulated slightly earlier than that of BMP-4.…”
Section: Shh/bone Morphogenetic Protein-4 Signaling Pathwaymentioning
confidence: 67%
“…In the early X. laevis embryos, Tolloid/ BMP-1 is known to regulate the activity of BMP-4 by degrading Chordin (Piccolo et al, 1997;Wardle et al, 1999;Blitz et al, 2000;Balemans and Hul, 2002). In the remodeling X. laevis intestine, we have shown that the mRNA expression of both Tolloid/ BMP-1 and Chordin appears to be weaker but up-regulated slightly earlier than that of BMP-4.…”
Section: Shh/bone Morphogenetic Protein-4 Signaling Pathwaymentioning
confidence: 67%
“…S1 in the supplementary material). Tolloid (BMP1-like) is a metalloprotease that activates Decapentaplegic (DPP; BMP2/4-like) signaling by inhibition of the BMP antagonist Short gastrulation (SOG; Chordin-like) (Ferguson and Anderson, 1992;Piccolo et al, 1997;Shimell et al, 1991;Wozney et al, 1988). smedsmad4-1 encodes a protein similar to the SMAD4 protein (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its expression temporally coincides with that of Tolloid/ BMP-1 (Shimizu et al, 2002) and a little earlier than that of BMP-4 (Ishizuya-Oka et al, 2001a), both of which have been identified as TH response genes that are expressed only in the connective tissue. In X. laevis early embryos, Chordin is degraded by Tolloid/BMP-1 and antagonizes BMP-4 activity in dorsoventral patterning of the body (Piccolo et al, 1997;Wardle et al, 1999;Blitz et al, 2000). Taken together, it is highly possible that BMP-4 activity during intestinal remodeling may be spatiotemporally regulated by Tolloid/BMP-1 through Chordin.…”
Section: Bmp-4 Activity Is Regulated By Th-induced Shh and Chordinmentioning
confidence: 99%
“…Although there are more than seven known antagonists of BMP-4 in vertebrates (Balemans and Hul, 2002), we used Chordin to inhibit BMP-4 activity, because it binds BMP-4 with a high affinity (Piccolo et al, 1996). In addition, we previously identified a Xenopus homolog of Drosophila Tolloid closely related to BMP-1 (Tolloid/BMP-1), which is known to degrade Chordin (Piccolo et al 1997;Wardle et al, 1999;Blitz et al, 2000;Balemans and Hul, 2002), as a TH response gene in the X. laevis intestine (Shimizu et al, 2002). Here, we show that Chordin is transiently expressed during intestinal remodeling and, by using its protein in vitro, that BMP-4 plays important roles in the adult epithelial differentiation as a connective tissue signaling factor.…”
Section: Introductionmentioning
confidence: 99%